PERANAN MANAJEMEN STRATEJIK DALAM MEMBESARKAN PERUSAHAAN KECIL - Patrick L. Setiadi (Bina Ekonomi, 2007)
Strategic management is management decisions that determine the fate of a company. Every company aiming to excel for a long time must always utilize strategic management continuously. According to Wheelen and Hunger, strategic management has more primitive forms. The application of strategic management requires allocation of company's resources. Only big companies like Astra International Tbk. and HM Sampoema Tbk. are able to dedicate sufficient human and financial resources for the application of strategic management, while small companies do not have such resources and only manage to use a more primitive form of strategic management, such as budget planning. According to Wheelen & Hunger, strategic management requires all levels in the organization to think strategically. This can only be done when the company has adopted information system to communicate strategic information from the top to the bottom level. Because almost all small companies do not have such information system, does this mean that they must content with budget planning and forget about strategic management? Is it true that small entrepreneurs starting from zero only use strategic management after their small companies become big? If it is true, then the contribution of strategic management in leading small companies to grow and become big companies is immaterial. This paper aims to present the contribution of strategic management in turning small companies into big companies.